Exercise intolerance — from spiroergometry to transdiaphragmatic myocardial punch biopsy: a case report of isolated cardiac sarcoidosis. Issue 1 (4th January 2021) - Schindler, Michael Johannes; Saguner, Ardan M; Benussi, Stefano; Bode, Peter Karl; Manka, Robert; Steffel, Jan; Tanner, Felix C; Zuber, Michel; Ruschitzka, Frank
Abstract: Background: Several aetiologies account for exercise intolerance, with cardiac sarcoidosis (CS) constituting a rare cause thereof. The pathogenesis of CS is still unresolved and its diagnosis still difficult to establish, in the absence of any extracardiac manifestations in particular. Case summary: A 49-year-old amateur athlete presented with exercise intolerance during running over a 3-week period. Coronary artery and structural lung disease were excluded by coronary angiography and computer tomography. The symptoms could be reproduced during spiroergometry during which an exercise-induced high-degree atrioventricular (AV) block was documented. During electrocardiographic monitoring, a 2:1 AV block was observed. Different imaging modalities showed inferobasal septal inflammation and fibrosis. Transthoracic and transoesophageal echocardiography-guided endomyocardial biopsies were inconclusive and only subsequent epicardial biopsy performed by transdiaphragmatic minimally invasive surgery lead to the histological diagnosis of non-caseating granuloma, confirming CS. The patient was treated with high-dose steroids 1 week after implantation of a primary prevention dual-chamber implantable cardioverter-defibrillator (ICD). While tapering steroids, recurrence of myocardial inflammation occurred. However, no tachytherapies and <0.1% right ventricular pacing were needed after 2 years of follow-up. Discussion: Differential diagnoses were either an infiltrative disease, a tumour, or an infectious disease. Due to the different treatment options, we had to establish definite diagnosis by myocardial biopsy. Retrospectively, the implantation of the ICD can be discussed. However, cardiac magnetic resonance imaging showed fibrosis which is usually irreversible and substrate for potentially lethal ventricular arrhythmia. Confirming the diagnosis of isolated CS is challenging. Long-term management should be guided individually based on clinical and imaging findings.